Representasi dan Dampak Kolonialisme dalam Film The East - Wulandari, Nur Astrid; Hidayatullah , Muhammad; Putra, Muh Rizal Ardiansah (Innovative: Journal Of Social Science Research, 2025)
This study aims to reveal the representation and impact of colonialism in the film The East (2020) through Charles Sanders Peirce's semiotic approach. This film depicts the Dutch military aggression after Indonesian independence and presents the perspective of the perpetrators of colonialism who experience inner conflict. The study uses a qualitative descriptive method with semiotic analysis techniques on visual, verbal, and narrative elements in the film. The results of the study show that signs such as KNIL uniforms, military posts, Dutch, and acts of violence are symbols of repressive and dehumanizing colonial domination. The impact of colonialism in this film is not only shown physically through events and violence, but also psychologically on the main characters and socio-culturally on the local community. This representation provides a deep understanding of colonialism as a system of power that not only controls territory, but also influences individual identity and morality. The film The East is present as a medium for criticism and reflection on the complex and traumatic colonial history.